La experiencia de una infraestructura financiera semi-formal en países en vías de desarrollo: propuestas para el Brasil y América Latina - Castro Carvalho, André (Pontificia Universidad Católica del Perú, 2013)
The government usually seeks help from private investors to be able to deliver public services. Private capital usually tends to concentrate on big profi table projects. In order to be able to carry out the smaller projects, an alternative to privatizations has to be proposed, in attention to the State’s inefficiency to deliver every service the society demands. In this article, the author proposes the civil society’s active participation as a way to carry out smaller projects efficiently. Nonetheless, civil participation is not possible without an attractive foment policy and the facilitation of particular initiatives given by the State. The article focuses particularly in the case of the Brazilian reality and other parts of LatinAmerica.

El Estado suele recurrir a la privatización para la implementación de servicios públicos. Generalmente, la inversión privada se concentra en grandes proyectos que le sean rentables. Se hace necesaria una alternativa al sistemade las privatizaciones, ya que el Estado tampoco puede asumir un rol activo en la prestación eficiente de todos los servicios que la sociedad demanda. En este artículo, el autor propone la participación activa de la sociedad civil para llevar acabo pequeños proyectos eficientemente. Sin embargo, ésta no es posible sin una correcta política de fomento y facilitación de iniciativas particulares por parte del Estado. Así, se pasa a analizar la situación de América Latina a la luz de la legislación y las experiencias internacionales.
Keywords: Law; Public Services; Infrastructure; Investment; Latin America; Civilian Collaboration; Servicios públicos; Infraestructura; Inversión; América latina; Participación civil; https://purl.org/pe-repo/ocde/ford#5.05.01